Goiters in Some Iraqi Females - Rashid , Saud; Alhiti, Hazim (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Goiter is a recognized disorder in females all over the world. This paper illustrates the goiter presentations of a sample of Iraqi females in one center in Al Anbar Provenance. Methods. This was a prospective, random collection of 320 Iraqi females in the general surgery outpatient clinic from Heet General Hospital between (1st August 2017 to 1st February 2019). We reported data after female/family consent to participate in the research, via direct clinical assessments, thyroid function tests, and goiter ultrasound. Results. Of 320 Iraqi females, eighty-six (26.8%) were in the peak age group (40-49). One hundred and twenty-six females had hypothyroid goiter (39.3 %), 141 females were euthyroid (44 %), and 53 females were hyperthyroid (16.5 %). Conclusion. Goiter is a common disorder among Iraqi females (especially in Al Anbar) that needs high clinical suspicion, government screening, and public awareness.